PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI GUGUS 1 BASKARA SUMIRAT SEMARANG - Vernando, Alexander Nova; Kaharudin, Erlitawati Kaharudin (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jawa Tengah, 2020)
Teacher performance plays an important role in the success of the National education program. This study aims to determine the effect of the principal's participatory leadership style and organizational culture on the performance of elementary school teachers. The entire population in this study was used as a sample, amounting to 80 elementary school teachers in Cluster 1 Baskara Sumirat Semarang. Data analysis used simple linear regression analysis. The results of the study prove that the principal's participatory leadership style and organizational culture have a positive and significant effect on teacher performance. The principal's participatory leadership style makes a significant contribution to teacher performance. Therefore, to improve teacher performance, the principal should try to implement participatory leadership behavior, besides that the principal also needs to improve his knowledge and skills about this leadership, either on his own initiative or on the initiative of the education institution office or other related parties.